Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T20:28:01+01:00
A)
{x+y= -4 --> y=-4-x
{2x+y=-5

2x-4-x=-5
x-4=-5
x=-1

y=-4+1=-3

{x=-1
{y=-3

b)
{3x-y=3 --> y=3x-3
{2x-3y=2

2x-3(3x-3)=2
2x-9x+9=2
-7x=-7
x=1

y=3*1-3
y=0

{x=1
{y=0

c)
{3x+2y=1
{x-2y=-5 --> x=2y-5

3(2y-5)+2y=1
6y-15+2y=1
8y=16
y=2

x=2*2-5
x=-1

{x=-1
{y=2
1 5 1
2010-03-17T20:34:31+01:00
A) x+y=-4
2x+y=-5 \×-1

x+y=-4
-2x-y=5

-x=1 \ ×-1
x=-1

y=-4-1
y=-5

b)
3x-y=3 \×-3
2x-3y=2

-9x+3y=9
2x-3y=2

-7x=7 \÷-7
x=-1

y=3-3*-1
y=3+3
y=6
c)
3x+2y=1
x-2y=-5

x=-5+2y
3x+2y=1

x=-5+2y
3(-5+2y)-1=-2y

x=-5+2y
-16=-8y \÷-8

x=-5+2 ×2
y=2

x=-1
y=2
1 3 1
2010-03-17T20:39:52+01:00
X+y= -4 | x (-2)
2x+y=-5
-2x-2y=-4
2x+y=-5
_______
y=9
x+y= -4
y=9
x=13
*********
3x-y=3 |x -3
2x-3y=2
-9x+3y=-9
2x-3y=2
_______
-7x=-7 (x=(-1))
2x-3y=2
-2-3y=2
x=1
3y=0
x=1
y=0
********
3x+2y=1
x-2y=-5
_______
4x=-4 (x=-1)
x=-1
x-2y=-5
x=-1
-1-2y=-5
x=-1
2y=-4
x=-1
y=-4


Prosze ^^

1 2 1